2015
DOI: 10.1124/jpet.114.222034
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine Substitution of Transmembrane Domain Amino Acids Alters the Ethanol Inhibition of GluN1/GluN2A N-Methyl-d-Aspartate Receptors

Abstract: N-Methyl-D-aspartate receptors (NMDARs) are inhibited by behaviorally relevant concentrations of ethanol, and residues within transmembrane (TM) domains of NMDARs, including TM3 GluN1 phenylalanine 639 (F639), regulate this sensitivity. In the present study, we used cysteine (C) mutagenesis to determine whether there are additional residues within nearby TM domains that regulate ethanol inhibition on NMDARs. GluN1(F639C)/GluN2A receptors were less inhibited by ethanol than wild-type receptors, and inhibition w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 37 publications
2
15
1
Order By: Relevance
“…Both mutant cycle analysis and two-way interaction ANOVA of mean open time values revealed an interaction between the positions, but the molecular mechanism underlying this interaction is unclear. Because GluN2A F636 and F637 are adjacent positions in the M3 domain alpha helix, the nature of this interaction differs from that of interactions we and others have reported between closely apposed side chains on separate M domains at intersubunit interfaces (Ren et al , 2012; Xu et al , 2015). In the latter instance, the distance between the interacting positions, as well as their orientation to one another, would change along with conformational changes associated with ion channel gating.…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations
“…Both mutant cycle analysis and two-way interaction ANOVA of mean open time values revealed an interaction between the positions, but the molecular mechanism underlying this interaction is unclear. Because GluN2A F636 and F637 are adjacent positions in the M3 domain alpha helix, the nature of this interaction differs from that of interactions we and others have reported between closely apposed side chains on separate M domains at intersubunit interfaces (Ren et al , 2012; Xu et al , 2015). In the latter instance, the distance between the interacting positions, as well as their orientation to one another, would change along with conformational changes associated with ion channel gating.…”
Section: Discussioncontrasting
confidence: 59%
“…Although there is no direct evidence that these positions form binding sites for ethanol, the ability of the positions to interactively and strongly regulate ethanol sensitivity is consistent with this view and provides the best evidence for this to date (Ren et al , 2012; Xu et al , 2015). Stronger evidence for this hypothesis awaits future studies demonstrating persistent alteration of NMDA receptor function by covalently-bound alcohol analogs or localization of ethanol or ethanol analogs to these positions using structural methods such as x-ray crystallography (Sauguet et al , 2013).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Our laboratory has reported that two positions in the GluN2A M3 and M4 domains can functionally interact to regulate ethanol sensitivity (Ren et al , 2008), and Smothers et al (2006) identified a pair of positions in the GluN1 subunit that can functionally interact with respect to ethanol inhibition. Positions at the intersubunit M3-M4 domain interfaces interact to regulate ethanol sensitivity and ion channel function (Ren et al , 2012), and can also form three-way interactions with M1 domain residues (Xu et al , 2015). Thus, multiple ethanol-sensitive positions appear to form sites of ethanol action.…”
Section: Discussionmentioning
confidence: 99%